Production systems alternative for triticale, under no-tillage, in Passo Fundo, RS, Brazil - Ambrosi, Ivo; Lhamby, Julio Cesar Barreneche; Baier, Augusto Carlos (Pesquisa Agropecuaria Brasileira, 1999)
From 1987 to 1991, in Passo Fundo, RS, Brazil, the effects of production systems on triticale crop were assessed at the Centro Nacional de Pesquisa de Trigo. Five systems for triticale were studied: system I (triticale/soybean), system II (triticale/soybean and black oats/soybean, from 1987 to 1989, and triticale/soybean and white oats/soybean, from 1990 to 1991), system III (triticale/soybean and common vetch/corn), system IV (triticale/soybean, black oats/soybean and common vetch/corn, from 1987 to 1989, and triticale/soybean, common vetch/corn and white oats/soybean, from 1990 to 1991), and system V (triticale/soybean, triticale/soybean, black oats/soybean and common vetch/corn, from 1987 to 1989, and triticale/soybean, triticale/soybean, common vetch/corn and white oats/soybean, from 1990 to 1991). An experimental design of blocks at random with three replications and plots with 24 m2 was used. Economic analysis over that period is presented in this paper. Over the period in which the climatic conditions were normal, system III was the best alternative to be offered to farmers from profitability standpoint. When climatic conditions were adverse, system II showed higher economic return, as compared to the remaining systems studied.